The potential role of beef and nutrients found in beef on outcomes of wellbeing in healthy adults 50 years of age and older: A systematic review of randomized controlled trials. (July 2022) - Hawley, Aubree L.; Liang, Xinya; Børsheim, Elisabet; Wolfe, Robert R.; Salisbury, Lutishoor; Hendy, Emma; Wu, Hexirui; Walker, Sam; Tacinelli, Angela M.; Baum, Jamie I.
Abstract: Shifts in wellbeing and health occur as we age. As life expectancy increases, maintenance of wellbeing and health becomes increasingly important. Nutrients found in beef are associated with outcomes of wellbeing such as physical and cognitive function, lean body mass, and mood in older adults and individuals with chronic disease. However, it is unclear how beef and nutrients found in beef impact wellbeing in healthy adults ≥50 years of age. This study systematically reviewed evidence linking the intake of beef and nutrients found in beef to markers of wellbeing in healthy adults. PubMed, CINAHL, and Web of Science were searched up to August 31, 2021 for eligible randomized controlled trials (RCTs). Nutrients included in the analysis were beef, red meat, dietary protein, essential amino acids, branched chain amino acids, tryptophan, arginine, cysteine, glycine, glutamate, vitamin B6, vitamin B12, choline, zinc, and iron. We identified nine RCTs with results from 55 measurements of markers of wellbeing. An overall positive effect was found of beef and beef's nutrients on wellbeing. There was an overall positive effect of amino acids and protein on wellbeing, with no effect of arginine, vitamin B-12, leucine, and zinc. Physical function was also influenced by beef and nutrients found in beef. Eight of the studies found focused on specific nutrients found in beef, and not beef itself in older adults with one or more chronic diseases. This study identified a need for further research regarding the effect of beef and nutrients found in beef on defined functional outcomes of wellbeing in healthy adults ≥50 years of age. Highlights: Shifts in wellbeing occur as we age. RCTs evaluating the effect of beef and nutrients in beef in healthy adults 50 years of age and older are highly heterogenous. Protein and amino acids positively influenced outcomes of quality of life and well-being. There is a lack of RCTs investigating the impact of beef and beef's nutrients on wellbeing in healthy adults 50 years of age and older.